The Hare and the Tortoise: Tackling Wireless Losses by Exploiting Wired Reliability - Badam, Anirudh; Han, Dongsu; Andersen, David; Kaminsky, Michael; Papagiannaki, Dina; Seshan, Srinivasan (MobiHoc'11, 2011)
Multiple communication channels are common in today’s consumer and enterprise networks. For example, a high bandwidth but unreliable wireless network might co-exist with a reliable wired link (EWLANs and neighborhood networks). In this paper, we present a system that uses this reliable wired communication channel to boost the bandwidth of the lossy wireless link. Specifically, we propose a new, efficient partial packet recovery (PPR) technique and adaptive feedback mechanism specially designed to correct partial packets on an 802.11 wireless network using a wired backhaul. Our initial experiments demonstrate up to a 3x improvement over standalone 802.11 and upto a 30% improvement over existing PPR techniques.